Green tea and its waste attract workers of formicine ants and kill theirworkers—implications for pest management - Dieng, Hamady; Ruzieyana, Bt Mohd Zawawi; Nur Intan Saidaah, Bt Mohamed Yusof; Abu Hassan, Ahmad; Fatimah, Abang; Idris, Abd Ghani; Tomomitsu, Satho; Hamdan, Ahmad; Wan Fatma, Zuharah; Abdul Hafiz, Ab Majid; Nur Shilawati, Abd. Latip; Cirilo, Nolasco-Hipolito; et al. (Elsevier B.V., 2016)
Daily, 3 billion cups of tea consumed worldwide and this consumption is accompanied by the discardingof huge waste amounts into the environment. Tea leaf contains a diverse array of toxic molecules. Despiteevidence that its waste is almost as rich in toxicants as green leaves; no research has been done to turnthis source of pollution into a benefit for ant pest management, where new chemistries are highly neededas a result on insecticide resistance. The present study was performed to explore the behavioral and lethaleffects of tea and its leftovers on the black crazy ant (BCA), Paratrechina longicornis Latreille, yellow crazyant (YCA), Anoplolepis gracilipes Smith, and weaver ant (WA), Oecophylla smaragdina Fabricius. Both freshtea extract (FTE) and used tea extract (UTE) were detrimental to the survival of BCA, YCA, and WA. FTEwas the most toxic solution and BCA was the most vulnerable species. The presence of tea extracts inmeals did not prevent workers of all three species from visiting and feeding in the presence their preferredfoods. The results presented here suggest that diets containing tea extracts are attractive to BCA, YCA, andWA when in competition with their preferred foods. These extracts were also insecticidal to the workerants. These properties demonstrate the potential of tea and its waste products for developing novelenvironmentally friendly and low-cost ant control strategies, which could also be a practical solution tothe growing environmental problem it causes.